Bimbingan Teman Sebaya Untuk Meningkatkan Interaksi Sosial Siswa Kelas X SMK PGRI 2 Denpasar Tahun Pelajaran 2022/2023 - I Made Mahaardhika; Ni Komang Sri Yuliastini; Nengah Ernawati (Journal Prakarsa Paedagogia, 2023)
This research aims to improve the Social Interaction of Class X Students of SMK PGRI 2 Denpasar for the 2022/2023 Academic Year through the Implementation of Peer Guidance. Students who were used as subjects in this study were students of class X Office Administration 1, totaling 42 students, focusing on 8 students who had low social interaction. This research is Guidance and Counseling Action Research on the implementation of peer guidance to improve students' social interaction. The research was conducted in two cycles. The implementation of the actions of each cycle consists of four main activities, namely: Action planning, Action implementation, Observation/evaluation, and Reflection. From the results of the research before the action obtained a score percentage of 49.5% and classified as low category, after being given the first cycle of action, it was found that there was an increase in student social interaction of 63.87% in the sufficient category, and in the second cycle there was an increase of 76 .25% in the high category. Based on the results obtained, it can be concluded that the Implementation of Peer Guidance can Increase the Social Interaction of Class X Students in Office Administration 1 SMK PGRI 2 Denpasar in the Academic Year 2002/2023.